THE INFLUENCE OF DEMOGRAPHICS, FINANCIAL LITERACY, AND FINANCIAL ATTITUDES ON PENSION FUND PLANNING AS AN INDEPENDENT ENTREPRENEURSHIP STRATEGY - Occha Putrie Safira; Yahya, Adibah; Oom Tikaromah (Universitas Sahid, 2025)
This study aims to analyze the influence of demographics, financial literacy, and financial attitudes on pension fund management in Cikarang Utara and Serang Baru Districts, Bekasi Regency. A quantitative approach with an associative method was employed, collecting data through closed questionnaires using a 5-point Likert scale. A sample of 60 respondents was obtained through purposive sampling. Data were analyzed using validity, reliability, normality, multicollinearity, heteroscedasticity, multiple regression, F-test, and t-test analyses. The results indicate that demographics, financial literacy, and financial attitudes simultaneously have a significant influence on pension fund management. Partially, age, financial literacy, and financial attitude have significant effects, while gender, education, and income do not. Financial attitude is the most dominant factor in pension fund management is explained by the three independent variables. These findings emphasize the importance of improving financial literacy and developing positive financial attitudes for optimal pension planning.